European overview of sustainable policies and approaches in COST C25 member countries - Gervásio, Helena Maria Santos (2011)
The implementation of the principles and methods towards a Sustainable Construction varies across different countries in Europe. In some countries, the sustainability of the construction sector has been effectively taken into consideration over the last years, while in other its implementation is at an initial stage. Many reasons may be pointed out for this situation. Different countries have different understandings of what is entailed in Sustainable Construction. Different cultural and educational backgrounds, along with different priorities in each country, are also contributing for the lack of a common European approach. General frameworks, aiming to cover every aspect of Sustainable Construction and to provide a consistent and integrated approach, such as Agenda 21 for Sustainable Construction, gave a major advance in the search for a common approach for the construction sector. However, general agreed methodologies and tools to make this common approach operational are still missing.